A multichannel metallic dual nano-wall square split-ring resonator: design analysis and applications. (26th November 2019) - Butt, M A; Khonina, S N; Kazanskiy, N L
Abstract: A multichannel metallic dual nano-wall square split-ring resonator is proposed for both filter and sensor applications. It is comprised of four square split-ring resonators which filter out wavelengths at 598 nm, 675 nm, 753 nm and 838 nm that are transmitted through respective ports connected to the rings. The proposed design is flexible, which allows the filtering of any desired wavelengths by varying the geometry of the ring. By incorporating the nano-walls in the ring, it is likely to excite the non-integer modes, which are not possible in regular rings. The transmission spectrum of the filter lies in a near-infrared region, which is a biological transparency window and makes it interesting for photo-thermal therapy applications. Due to its design benefits, this structure can also be used in biosensing applications. The best sensitivity, Q -factor and figure of merit of the sensor is obtained at 793.3 nm/RIU, 82.1 and 52.9, respectively.